(untitled) (Journal of Philosophy Culture and Political Science, 2026)
The article is devoted to the study of the philosophy of Kazakh musical creativity in the context of cultural transformation of modern society. Entering the era of digital civilization, the Kazakh musical tradition faces the challenge of preserving its identity amid rapid globalization and technological changes. The aim of the work is to identify the main directions of transformation of the musical culture of the Kazakh people and to comprehend its role as a means of cultural communication and preservation of ethnic identity. The research is based on an interdisciplinary methodology combining approaches from cultural studies, musicology, philosophy, information technology, and pedagogy. Methods of content analysis, comparative-historical and system analysis, as well as a synergetic approach focused on the study of self-organization processes in culture are applied. The research focuses on: analysis of the impact of digitalization on the forms of existence of musical art; rethinking of musical memory under conditions of information oversaturation; study of the peculiarities of music perception when applying musical-computer technologies; assessment of new opportunities and risks for the preservation and development of the Kazakh musical tradition. The study revealed that Kazakh musical creativity in the digital age undergoes a dual process: on the one hand, there is a threat of loss of authenticity, on the other, prospects for repopularization and revitalization of traditional culture through digital communication channels are emerging. Digitalization promotes the creation of new forms of artistic representation – digital archives, virtual concerts, digital operas, and synthetic interdisciplinary projects. The scientific significance lies in the development of a theoretical model for interpreting Kazakh musical art as a living communicative cultural code capable of adapting and evolving in new informational conditions. The practical significance is manifested in the possibility of applying the findings for educational programs aimed at preserving national musical culture, for designing digital platforms for promoting Kazakh musical heritage, as well as for cultural policy and art management. Key results include the substantiation of the concept of polymodality of musical perception, which enables effective use of digital technologies for deeper immersion into traditional art forms, and the analysis of mechanisms of musical memory transformation in the era of clip thinking and information surplus. In conclusion, it is emphasized that the philosophy of Kazakh musical creativity, viewed through the prism of cultural transformations, not only retains its relevance but also acquires new forms of existence in the digital reality. The conducted research contributes to the development of national cultural science, opening prospects for further studies in the fields of digital socialization and philosophy of art. Key words: socio-cultural transformation, digitalization of art, clip thinking, symbol inflation, polymodality of perception